Comparative Analysis of Income on Palm Oil Production Between the Land Application (LA) and Non Land Application (NLA) Waste Management in Lubuk Dalam Estate Of PTPN V, Siak District, Riau Province, Indonesia - E Tety; A Rifai; TH Rasyid; Yeni Kusumawaty; S Tarigan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
This study aimed to compare the level of income on the production of Fresh Fruit Bunches (FFB) for Land Application (LA) and Non-Land Application (NLA) fields. The data used was secondary data from the company in terms of information on the area of palm oil plantations, palm oil production, waste production, and the spread of palm oil liquid waste. Data analysis applied analysis of production, depreciation, cost analysis, revenue, net income, and production efficiency. Based on the results of the study, FFB income in PTPN V Lubuk Dalam Estate from Land Application (LA) field was IDR 51,816,821 / ha/year, which was higher than the income from the Non-Land Application (NLA) field of IDR 33,073,190 / ha/year. In conclusion, PTPN V Lubuk Dalam Estate received higher income by applying LA waste management compared to Non-Land application (NLA).